Comparative study of the effect of silica nanoparticles and polystyrene on the properties of concrete - Alaa N. Saleh; Alyaa A. Attar; Sameer Algburi; Omer K. Ahmed (Results in Materials, 2023)
The current article examined the effect of adding nano silica and polystyrene granules on the compressive strength and thermal conductivity of concrete. Nano silica and polystyrene granules were added in proportions (1%, 2%, 3%) to the concrete mixture, and the compressive strength and thermal conductivity of the concrete mixtures were examined. The results showed when silica nanoparticles were added, the compressive strength increased, however when polystyrene granules were added, the compressive strength decreased. The thermal conductivity of concrete by adding nano silica and polystyrene granules ranged within (0.43–0.45) W/m. oC. The best percentage of silica nanoparticles (SiO2) and polystyrene granules can be added to concrete to obtain the maximum compressive strength values, which amounted to (3%) and (0.8%), respectively.